The impact of intervention strategies that target arterial stiffness in end-stage renal disease: a systematic review protocol. Issue 1 (December 2016) - Rodriguez, Rosendo; Shea, Beverley; Hae, Richard; Burns, Kevin
Abstract Background/objectives Vascular damage contributes to the high cardiovascular morbidity and mortality in end-stage renal disease (ESRD). Increased aortic stiffness measured by carotid-femoral pulse wave velocity (cf-PWV) is a strong and independent predictor of the cardiovascular risk in ESRD patients. Recently, there has been considerable interest in developing strategies to lessen the progression of arterial stiffness in ESRD patients using cf-PWV as a tool to monitor therapeutic responses, but their benefit on the long-term cardiovascular risk is not known. Appraisal of the effects of existing stiffness-based interventions on the cf-PWV would facilitate selecting optimal therapies to be tested in randomized clinical trials. The aim of this systematic review will be to evaluate the impact of arterial stiffness-based interventions on the cf-PWV in ESRD patients. Secondarily, for each intervention, we will determine the minimal duration needed to achieve a significant reduction of cf-PWV, the minimal cf-PWV reduction threshold or effect size, and adverse events. Methods/design This review will be conducted using MEDLINE, EMBASE, and EBM Reviews. We will select clinical trials and observational studies (cohort, case-control, and before/after studies and case series) that evaluated pharmacologic or non-pharmacologic interventions in which the primary effect is to improve structural and/or dynamic components of arterial stiffness in adults with stage 5 chronic kidney disease. The primary outcome of interest will be cf-PWV. Study selection and data collection will be performed by two reviewers. Validated tools will be used to assess the methodological quality and risk of bias among different study designs. We will describe all included citations according to study characteristics, methodological quality, and outcomes. Suitability for meta-analysis will be determined by the degree of clinical and statistical heterogeneity between studies. If appropriate, we will calculate effect estimates by obtaining the relative risks with 95 % confidence intervals pooled according to study design using a random effects model. Discussion This review will summarize evidence regarding effects of interventions targeting arterial stiffness in ESRD patients. Our results will inform clinicians and researchers on the type of existing arterial stiffness-based interventions for ESRD patients and their potential efficacy and safety, with a goal to guide future clinical trials aimed at reducing adverse cardiovascular events. Systematic review registration PROSPEROCRD42016033463